Women, Administered Insecurity, and Multiple Alignments to Assuage Gender Inequalities in the Brazilian Zika Epidemic - Scott, Parry (Frontiers in Global Women's Health, 2021)
This article deals with the Brazilian Zika epidemic that started in 2015 and became an important event for understanding Gender and Power in health treatment contexts. It discusses a combination of reinforcement of gender normed care and therapeutic itineraries overburdening mothers and the construction of political awareness and practice associated with demands for state services. Working with a concept of administered insecurity elaborated to understand people displaced during the implementation of planned government development policies, it argues that the planned nature of health systems, despite their explicit emphasis on the objective of treating the health of the population, also generate administered insecurity as planned administrators of scarcity. It uses data from a 4-year research project entitled “Doing Ethnography on Care” in Recife, Brazil, to show the multiplicity of contexts that are brought out through the practice of mothers in providing care for their Zika-syndrome stricken children, and how they reflect varying power relations that constantly re-dimension maternity along lines of gender relations in different institutional domains of treatment and research. The severe gender inequality in caring for infants was partially assuaged by multiple alignments made by the mothers and infants promoting dialogue and practice in varied contexts, including interaction with the research team. Family and Community Relations, Mediation, Favors, Accusations, Judicialization, Collective Action, formation of Associations, and learning to produce videos are seen as constructors of complex meaning and practice of mothering in a way in which gender goes beyond the limits of an overburdening practice of care. Gender provides a significant difference for mothers whose knowledge and familiarity of domains of health and health-related provision of services and knowledge, forged in their search for treatment for their child, create and legitimate spaces for the exercise of informed citizenship and a sharp awareness and resistance to practices by the state and other agents who administer insecurity. The final remarks synthesize some of the more important reconfigurations of gender relations and power in the context of the Zika epidemic and alerts to the challenge of the transitory nature of an epidemic and the gradual, and not so gradual, exhaustion of institutional interest for the dilemma of the mothers and also shows the role of anthropological research in promoting gender equality in epidemic contexts.